Strategies to support health professionals in the condition of second victim: scoping review - Quadrado, Ellen Regina Sevilla; Tronchin, Daisy Maria Rizatto; Maia, Flávia de Oliveira Motta (Revista da Escola de Enfermagem da USP, 2021)
Objective: To map and analyze the knowledge produced about strategies aimed at promoting support to health professionals in the condition of second victim. Method: Scoping review, developed in portals, databases and academic websites, whose inclusion criteria were articles and materials indexed in the respective search sites, between January 2000 and December 2019, in Portuguese, English and Spanish. The findings were summarized and analyzed based on descriptive statistics and narrative synthesis. Results: A total of 64 studies were included, 100% international; 92.2% in English and 50% from secondary research. The support strategies were grouped into four categories and most of the studies referred to the use of the forYOU, Medically Induced Trauma Support Services and Resilience in Stressful Events programs and the interventions represented, through dialogue with peers, family, friends and managers. Conclusion: Support strategies for the second victim are pointed out in international studies and mostly developed through programs/services and interventions. It is recommended to develop studies to learn about the phenomenon and to structure feasible support strategies in Brazilian health organizations.